The Impact of Employee Wellness Programs and Management Support on Stress Levels and Work Performance: Evidence from the Manufacturing Industry - Dwi Nadini Saputri; Dwi Astuti (Lentera Ilmu Nusantara, 2026)
This study aims to analyze the effect of employee wellness programs and management support on the level of work stress and employee performance in the manufacturing industry. This research is motivated by the characteristics of the manufacturing industry work environment which has high work pressure, heavy workloads, and continuous productivity demands, thus potentially increasing employee work stress levels. The research method used is a quantitative approach with a survey method through the distribution of questionnaires to employees in manufacturing plants. The research data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software version 3.0. The results of the study indicate that employee wellness programs and management support have a significant effect in reducing work stress levels and improving employee work performance, both directly and indirectly. The findings of this study provide practical implications for manufacturing industry management in designing and implementing employee wellness programs integrated with human resource management strategies. Thus, companies are expected to be able to create a supportive work environment, reduce the risk of burnout and turnover, and increase employee productivity and quality of performance in a sustainable manner.